2022
DOI: 10.21157/ijtvbr.v6i1.25205
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance, Piglet Mortality and Reproductive Health Problems of Sows in The Ejisu Municipality

Abstract: A cross-sectional study was conducted among commercial pig farmers in the Ejisu Municipality to investigate reproductive performance, piglet mortality, and reproductive health problems on their farms. Questionnaires designed to obtain information on reproductive performance and reproductive health problems were administered to a total of 50 randomly selected pig farmers. Three farms were randomly selected to monitor farrowing and pre-weaning piglet mortality. The farrowing records of a minimum of 10 sows on ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In Ghana, Ascaris lumbricoides has been identified in children at the hospital (Mirisho et al., 2017), school children (Orish et al., 2019), inhabitants of an orphanage (Duedu et al., 2015) and pregnant women (Abaka‐Yawson et al., 2020). Even though there is sparse information on Ascaris infection in livestock, studies have detected this parasite in goats, cattle and pigs (Atawalna et al., 2016; Futagbi et al., 2015; Mensah et al., 2018). In this study, the significant difference between the prevalence of Ascaris infection of the weaners and the boars, sows and piglets, and the sows and weaners could be due to the acquired immunity obtained by both the boars and sows over a consistent period of exposure to the source of infection.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, Ascaris lumbricoides has been identified in children at the hospital (Mirisho et al., 2017), school children (Orish et al., 2019), inhabitants of an orphanage (Duedu et al., 2015) and pregnant women (Abaka‐Yawson et al., 2020). Even though there is sparse information on Ascaris infection in livestock, studies have detected this parasite in goats, cattle and pigs (Atawalna et al., 2016; Futagbi et al., 2015; Mensah et al., 2018). In this study, the significant difference between the prevalence of Ascaris infection of the weaners and the boars, sows and piglets, and the sows and weaners could be due to the acquired immunity obtained by both the boars and sows over a consistent period of exposure to the source of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Reproductive health problems often occur in the field and have an impact on livestock populations. Previous studies show that reproductive health problems are serious problems that need to be addressed in the field (Atawalna et al, 2021). Furthermore, previous research reported that several factors that greatly influence the high and low reproductive rates of livestock include age at puberty, conception rate, calving interval, service period, services per conception, calving rate, and duration of pregnancy (Pohontu et al, 2018;Yusri, 2020) Pig reproductive health problems are a serious problem that farmers need to know about.…”
Section: Introductionmentioning
confidence: 99%

Reproductive Health Counseling for Gilt and Sow

Feribertus Rinca,
Ingrida Velisia Amul,
Kosmas Ardino
et al. 2024
IJCSL